Best Answer

There can be no answer since there is no equation: only an expression. It is possible to factorise the expression as follows:

6x2 - 5x - 11 = 6x2 + 6x - 11x - 11 = 6x(x + 1) - 11(x + 1) = (x + 1)(6x - 11)

Just to add, if you meant 6x2 - 5x - 11 = 0, then the above factorise would give you either (x+1) = 0, or (6x-11)=0, so x=-1 or 11/6

Study guides

☆☆

Q: What is the answer to 6x squared minus 5x minus 11?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

4x3+10x2-6x 2x(2x2+5x-3) 2x(2x-1)(x+3)

0. 6x + 3 = 5x + 141. 6x = 5x + 11 [subtracting 3]2. x = 11 [subtracting 5x]

6x2-5x-21 = (3x-7)(2x+3)

When factored it is: (6x-1)(6x+1)

-116

Related questions

(3x + 2)(2x - 3)

(2x + 1)(3x - 4)

6x2 + 5x - 6 is factored out to (2x + 3)(3x - 2).

5x + x = 5x Squared (5x^2) x + x equals 2 x's = 2 = squared - very simple & logic. no its not simple and logic 5x^2 is the result of 5x times x. 5x plus x is 6x. Think of the x as 1x not x so 1x + 5x= 6x. That's simple and logic.

4x3+10x2-6x 2x(2x2+5x-3) 2x(2x-1)(x+3)

0. 6x + 3 = 5x + 141. 6x = 5x + 11 [subtracting 3]2. x = 11 [subtracting 5x]

x = 0,1

Assuming you mean x squared plus 5x squared... the answer is 6x squared.

6x3 - 5x = x*(6x2 - 5)

When factored it is: (6x-1)(6x+1)

6x2-5x-21 = (3x-7)(2x+3)

4x2 + 5x + 1 - 4x2 - 6x = - x + 1 or 1 - x4x2 + 5x + 1 - 4x2 - 6x = - x + 1 or 1 - x4x2 + 5x + 1 - 4x2 - 6x = - x + 1 or 1 - x4x2 + 5x + 1 - 4x2 - 6x = - x + 1 or 1 - x

People also asked